C-reactive protein provides superior prognostic accuracy than the IMDC risk model in renal cell carcinoma treated with Atezolizumab/Bevacizumab - Abuhelwa, Ahmad Y.; Bellmunt, Joaquim; Kichenadasse, Ganessan; McKinnon, Ross A.; Rowland, Andrew; Sorich, Michael J.; Hopkins, Ashley M. (Frontiers in Oncology, 2022)
Background Immune check-point inhibitors (ICIs) is a main treatment option for patients with metastatic renal cell carcinoma (mRCC); however, significant heterogeneity in response is commonly observed. This study aimed to evaluate the ability of C-reactive protein (CRP) to predict overall survival (OS) and progression free survival (PFS) in patients with mRCC treated with immunotherapy. Patients and methods Data from patients with mRCC treated with atezolizumab plus bevacizumab in the IMmotion150 and IMmotion151 trials were pooled. Cox proportional regression was used to model prognostic associations. The relative importance of CRP against IMDC factors was confirmed using machine learning. Results CRP were available from 527 patients (mean[range] CRP 6.3[0.21-340]mg/L). Elevated CRP was significantly associated with worse OS (HR[95%CI] 1.71[1.54-1.90],P<0.001) and PFS (1.27[1.18-1.35],P<0.001). CRP was the most prognostic factor for survival within the available clinicopathological data. The prognostic performance of CRP was superior to IMDC model for OS (CRP c=0.76, IMDC c=0.67,P<0.001) and PFS (CRP OS c=0.62, IMDC c=0.59,P=0.03). Predicted 2-year OS probabilities for patients with CRP values of 0.5, 5, 40, 150mg/L were 96%, 73%, 42%, 23% respectively. Conclusions CRP is a powerful prognostic marker for survival and its prognostic value was superior to the IMDC risk model. This study highlights that CRP could be implemented as stratification factor for mRCC immunotherapy trials and potentially as an easy to use prognostic tool in the clinic.